PP16 Representations, Stimulus And Constraints Of The Football Referee. (21st October 2014) - Sarmento, H; Marques, A; Pereira, A
Abstract : Although athletes have been the focus of thousands of studies in the field of sport psychology and sociology, referees have been sorely neglected. This is unexpected because referees are important sport participants. Those behaviour and decisions can have an important impact on game outcomes. The main aim of this study was to know the representations, stimulus and constraints of football referees. Nineteen Portuguese non-professional referees were inquired using semi-structured interviews. Ages ranged from 18 to 39 years (M = 29, SD = 6). Data analysis was performed using content analysis (Bardin, 2008), and through combining inductive and deductive approaches, the text units were coded and text units with comparable meanings were organised into specific categories. Three researchers conducted the analysis independently to ensure that the resulting classification system was suitable and best fitted the data. The software QSR NVivo 10 was used in coding the transcripts of the interviews. Result analysis allowed concluding that referees believe what represents themselves, mostly, is passion for football, enjoying their job but also the ethic and deontological values associated with this activity. Values such as trustworthy, fairness, responsibility, respect and dignity are highly appreciated among them. It was referred that a good referee must be well prepared physically, but psychologically as well to enhance their performance. The majority of the interviewed feels encouraged to perform their referee activities, quoting career progression and appreciation for the refereeing as main incentives. Those not encouraged, mentioned low salaries and not being respected or supported by other colleagues. These constraints have led the interviewers to consider quitting at some point. The present research offers preliminary support for the role of some important representations, stimulus and constraints of football referees. Future research on this field would thus appear to be promising.